PENGARUH PERPUTARAN KAS, PIUTANG, DAN PERSEDIAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN FOOD AND BEVERAGE DI BURSA EFEK INDONESIA (BEI) - Lorenza, Della Olivia; Winedar, Mustika (Politeknik Negeri Ambon, 2025)
Introduction: This research investigates the impact of elements of working capital (including cash turnover, receivables turnover, and inventory turnover) on the profitability of food and beverage firms listed on the Indonesia Stock Exchange (IDX). Profitability, measured by Return On Asset (ROA), plays a crucial role in evaluating business performance and investment attractiveness. Efficient turnover in cash, receivables, and inventory is enhancing the company's profit margins and operational sustainability. Therefore, this study aims to provide empirical evidence regarding the association between these indicators and profitability.Methods: This is a quantitative study using secondary data derived from the financial statements of food and beverage companies listed on the IDX during the 2022-2024 period. A total of 132 companies were considered, and 50 samples were selected using purposive sampling based on predefined criteria. Data analysis was conducted using multiple linear regression with the help of SPSS 25 Software. The study performed classical assumption test such as normality, multicollinearity, heteroscedasticity, and autocorrelation to ensure the validity of the regression model.Results: The results indicate so that, simultaneously, cash turnover, accounts receivable turnover, and inventory turnover significantly impact the company's profitability (ROA). Partial tests reveal that each of the three independent variables additionally contributes positively and significantly to ROA. The coefficient of determination (R²) is 0.843, meaning that the three turnover variables explain 84.3% of the variability in profitability. This highlights the importance of efficient working capital management in enhancing firm performance. Keywords: Accounts Receivable Turnover, Cash Turnover, Inventory Turnover, Profitability